Pengaruh Suhu Pemeraman terhadap Kinerja Fly Ash untuk Tanah Lempung Lunak - Auli, Septriza; Putra, Andius Dasa; Syah, Aminudin; Iswan, Iswan (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
One of the construction problems that is often encountered in the world, including Indonesia, is the construction of highways carried out on soft soil subgrade. In general, the improvement of soft subgrade is carried out with special modifications or handling, one of which is by stabilization so the subgrade can be used based on the standards. The use of fly ash as a stabilization material is considered an effective option because of its economical price and the elements in it have the ability to harden and increase strength when reacting with water. This study aims to find out the improvement of soft soil quality that has been mixed with several variations of fly ash seen from parameters such as Atterberg Limits and CBR. By reviewing the highest temperature conditions that ever happened in Indonesia based on Badan Meteorologi dan Geofisika (BMKG) and relating it with temperature conditions in the field, the study also reviewed the influence of high temperatures of 40°C on these parameters. The results are a decrease in the maximum dry density and an increase in the optimum moisture content. In addition, the value of the Atterberg Limit decreased significantly. The largest CBR value is shown in the addition rate of fly ash by 10% with a 7-day curing time at a temperature >40°C.Keywords: soft soil, soil stabilization, fly ash, high curing temperature, CBR